2021
DOI: 10.3390/ijms222212572
|View full text |Cite
|
Sign up to set email alerts
|

PODNL1 Methylation Serves as a Prognostic Biomarker and Associates with Immune Cell Infiltration and Immune Checkpoint Blockade Response in Lower-Grade Glioma

Abstract: Lower-grade glioma (LGG) is a diffuse infiltrative tumor of the central nervous system, which lacks targeted therapy. We investigated the role of Podocan-like 1 (PODNL1) methylation in LGG clinical outcomes using the TCGA-LGG transcriptomics dataset. We identified four PODNL1 CpG sites, cg07425555, cg26969888, cg18547299, and cg24354933, which were associated with unfavorable overall survival (OS) and disease-free survival (DFS) in univariate and multivariate analysis after adjusting for age, gender, tumor-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
1
6
0
2
Order By: Relevance
“…PODNL1 is an important member of the SLRP family which includes ubiquitous ECM components involved in matrix organization and signaling regulation in TME [4]. At present, a number of studies have revealed the promoting role of PODNL1 in tumor proliferation and EMT [14][15][16][17][18]. In high-grade glioma cell lines, PODNL1 has been demonstrated to stimulate cell proliferation and migration via the regulation of the Akt-mTOR axis [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PODNL1 is an important member of the SLRP family which includes ubiquitous ECM components involved in matrix organization and signaling regulation in TME [4]. At present, a number of studies have revealed the promoting role of PODNL1 in tumor proliferation and EMT [14][15][16][17][18]. In high-grade glioma cell lines, PODNL1 has been demonstrated to stimulate cell proliferation and migration via the regulation of the Akt-mTOR axis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, SLRPs have a class V member, named podocan-like 1 (PODNL1), which is found to be highly expressed in bone, glioma, bladder and ovarian cancers, representing a potential prognostic biomarker [14][15][16][17][18]. Its high expression together with the presence of low-methylation in its CpG sites is coupled with significantly increased expressions of PD-1, PD-L1, and CTLA4 in glioma [17]. Its overexpression in glioma cells is even believed to remarkably promote the mesenchymal-related biomarkers including vimentin, N-cadherin, snail, and fibronectin [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al demonstrated that hypermethylation of the miR-338-5p promoter regulated the aberrant expression of ETS-1, which was a key regulator of tumor cell proliferation and invasion, and was associated with prognosis of astrocytoma patients (35). There was also a public database-based bioinformatics analysis showing that PODNL1 methylation acted as a prognostic biomarker and correlates with immune infiltration and immune checkpoints in LGG (36). da Costa Rosa et al evaluated the effect of a DNA demethylating agent combined with all-trans retinoic acid in IDH1 mutant gliomas, and the combination of 5-Aza and atRA reduced the growth of IDH1 R132H glioma cells and increased differentiation and apoptosis (37).…”
Section: Discussionmentioning
confidence: 99%
“…No tecido muscular destacamos o aumento da expressão dos genes EDN1, MRC1, CDC6 e CCBE1 e a redução da expressão dos genes SPATA3, TNP2, FSCB, PRM2, IQCF1 e CDKN1A O gene PODNL1 (Podocan Like 1) pertence à família dos pequenos proteoglicanos ricos em leucina (SLRP). Ainda não tem função conhecida, mas pode estar associada a processos que envolvam a matriz extracelular (NOOR et al, 2021). Em humanos, é um marcador de prognóstico de câncer de ovário (TENG; ZHENG, 2017) e glioma (NOOR et al, 2021).…”
Section: Discussionunclassified
“…Ainda não tem função conhecida, mas pode estar associada a processos que envolvam a matriz extracelular (NOOR et al, 2021). Em humanos, é um marcador de prognóstico de câncer de ovário (TENG; ZHENG, 2017) e glioma (NOOR et al, 2021). É expresso em diversos tecidos, com maiores níveis em placenta e testículos (FAGERBERG et al, 2014).…”
Section: Discussionunclassified